Legal Capital of Enterprise under tha laws of Viet Nam - HO, Thang X (Open Science Journal, 2020)
It can be said that business investment capital is always the most important requirement for investors to enter the market that developing countries in the market economy like Vietnam cannot ignore. But the question is how much minimum capital threshold to allow investors to enter the market is not a simple issue that many countries' business laws must consider to make appropriate adjustments.